Werte in de natur und die natur der werte - Rolston, Holmes, 1932-2025, author; Suhrkamp Verlag, publisher (Colorado State University. Libraries, 1997)
Value is often thought not to exist in wild nature; it is bestowed on nature by human preferences. This prevailing account is too anthropocentric. In nature, animals value their lives; they too can have their preferences satisfied. Plants have vital needs. Species are historical forms of life defended over generations. Ecosystems are "able to generate value," as occurs with the evolution and ecological support of organisms, animals, and humans. Earth, taken as earth, dirt, seems of little intrinsic value; but Earth, the home planet, is systemically valuable, the ground of all value.
Value in nature and the nature of value
Text in German.
Keywords: organisms; species; humans; environmental values; environmental ethics; ecosystems; philosophy of nature